Uji Validitas Konstruk Multidimensional Scale of Perceived Social Support (MSPSS) melalui Confirmatory Factor Analysis (CFA) - Zefanya Cheline Saragih; Ayu Rifqi Indah G; Nurul Lisa Isnaini (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Social support is defined as an individual’s perception of the availability and presence of assistance derived from three primary sources, namely family, friends, and individuals considered significant others. This concept emphasizes the subjective evaluation of the quantity and quality of support perceived by individuals, rather than the actual support provided. This study aims to examine the construct validity of the Multidimensional Scale of Perceived Social Support (MSPSS) developed by Zimet et al. (1988), which has been adapted into the Indonesian language. The MSPSS instrument is designed to measure the extent to which individuals perceive social support received from family, friends, and significant others in their lives. Research participants were selected using a purposive sampling technique, with inclusion criteria consisting of active university students aged between 18 and 27 years. A total of 279 students participated in this study. The research employed a quantitative approach, with data collected through an online questionnaire administered via Google Forms and distributed through various social media platforms. Data analysis was conducted using Confirmatory Factor Analysis (CFA) with the assistance of Jamovi software.